COMPARISON THE EFECTIVENESS OF PHYSICAL THERAPY AND CORTICOSTEROID INJECTION FOR SUBACROMIAL IMPINGEMENT SYNDROME - Funda Levendoğlu,; Halim Yılmaz,; Hatice Uğurlu, (Archives of Rheumatology, 2005)
Objective: We compared the effectiveness of corticosteroid injections with physical therapy for the treatment of subacromial impingement syndrome. Methods: Fifty-two patients with subacromial impingement syndrome were enrolled in the study. Patients were randomly divided into two groups. Corticosteroid injection consisted of an injection of 1 ml of 40 mg/ml triamcinolone acetonide in combination with 4 ml of %1 lidocain . Corticosteroid injection was given from the lateral side to the subacromial region in the first group. Physical agents consisting of ultrasound, TENS, hotpack were performed to the second group. Codman and strengthening exercises were given to the both groups. All patients were reviewed at 15 day, 1 and 3 months after the beginning of the therapy. For the evaluation of pain intensity Visual Analogue Scale (VAS), for the assessment of maximal muscle strength isokinetic measurement, for the assessment of shoulder function American Shoulder and Elbow Surgery (ASES) Shoulder Index Scale were utilized. Results: There was a significant reduction in patient's pain scores in both treatment groups. But, pain reduction was significantly higher in injection group when compared the physical therapy group (p<0.05). Comparison of the other parameters between injection group and physical therapy group found no statistical difference at 15 day, 1 and 3 months (p>0.05). Conclusion: There was a greater pain reduction in patients with treated steroid injections. But, both physical therapy and local steroid injections were of similar effectiveness for shoulder functions.